The impact of corporate taxes and flexibility on entrepreneurial decisions with moral hazard and simultaneous firm and personal level taxation - Fabian Meißner; Georg Schneider; Caren Sureth (Arbeitskreis Quantitative Steuerlehre (arqus), 2013)
In this paper we investigate the incentive effects of corporate taxes in an agency setting with a principal facing an investment opportunity including an abandonment option. We are particularly interested in the interplay of taxation and the real option on the principal's incentives to motivate the agent to work hard. First, we extend the well-known studies on tax effects on decision making under uncertainty to moral hazard settings. In a benchmark case we find that, as confirmed in current literature, the corporate income tax has no incentive effect. If the principal accounts for the real option we show that paradoxical tax effects may occur. Also, with respect to the effect of the real option on the incentive problem we show that the option makes it less attractive for the principal to induce the agent to exert a high effort.
Keywords: 330; Tax Effects; Real Options; Moral Hazard; Investment Decisions